A Review: Peptide-Based Hydrogels Biomaterials: From Synthesis to Biomedical Applications - Sari, Nasmi Herlina; Rivlan, Muhammad Zaidan Fadhlurrohman; Thiagamani, Senthil Muthu Kumar (Journal of Fibers and Polymer Composites, 2025)
Peptide-based hydrogel biomaterials (BHP) have emerged as novel therapeutic platforms for biomedical applications, providing accurate, efficient, and regulated drug delivery. This review examines the design, characterization, production, and biomedical applications of BHP, emphasizing their potential benefits in biomedicine. Advances in peptide synthesis techniques have permitted the creation of hydrogels with customized physicochemical properties to satisfy specific biomedical needs. Furthermore, this review delves into BHPs' biomedical uses, focusing on their role in improving therapeutic responses, allowing for sustained drug release, and reducing tumor growth. BHPs, with their biocompatibility, programmable hydrogel production, and adaptability, constitute a viable technique for addressing the problems of ovarian cancer treatment. This paper gives a thorough summary of current achievements in BHP research, bridging the gap between material development and clinical applications.